1990
DOI: 10.1128/jb.172.4.1969-1977.1990
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of a putative Escherichia coli [NiFe] hydrogenase-1 operon containing six open reading frames

Abstract: DNA encompassing the structural genes of an Escherichia coli [NiFe] hydrogenase has been cloned and sequenced. The genes were identified as those encoding the large and small subunits of hydrogenase isozyme 1 based on NH2-terminal sequences of purified subunits (kindly provided by K. Francis and K. T. Shanmugam). The structural genes formed part of a putative operon that contained four additional open reading frames. We have designated the operon hya and the six open reading frames hyaA through F. hyaA and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
90
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(93 citation statements)
references
References 41 publications
(17 reference statements)
3
90
0
Order By: Relevance
“…6). HmcB, which has an N-terminal 'twin-arginine' signal sequence, is located at the periplasmic face of the cytoplasmic membrane to [25]; hups, hupS gene product from R. capsulatus [26]; hyaa, hyaA gene product of hydrogenase 1 from E. coli [7] ; hynb, hynB gene product from D. gigas [61; hyb0, small subunit of E. coli hydrogenase 2 [23]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6). HmcB, which has an N-terminal 'twin-arginine' signal sequence, is located at the periplasmic face of the cytoplasmic membrane to [25]; hups, hupS gene product from R. capsulatus [26]; hyaa, hyaA gene product of hydrogenase 1 from E. coli [7] ; hynb, hynB gene product from D. gigas [61; hyb0, small subunit of E. coli hydrogenase 2 [23]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fax: (33) 91 71 89 14. E-mail: wu@ibsm.cnrs-mrs.fr HYD2 and HYD3 activities, respectively [2][3][4][5]. All three hydrogenases contain nickel [1,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Three immunologically and genetically distinct [NiFe] hydrogenases, termed hydrogenase 1, hydrogenase 2 and hydrogenase 3, have been identified and characterized in Escherichia coli , 1986Sawers et al, 1985 ;Bo$ hm et al, 1990 ;Menon et al, 1990Menon et al, , 1994Sauter et al, 1992). More recently, the existence of a fourth enzyme has been postulated based on a genetic analysis of the E. coli chromosome (Andrews et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It is apparent from its subunit structure and from its overall amino acid sequence similarity with other uptake hydrogenases that it has a role in hydrogen oxidation (Menon et al, 1990). It has been proposed to be involved in recycling the hydrogen produced by hydrogenase 3 based on the fact that its synthesis shows a strong correlation with that of the FHL pathway (Sawers et al, 1985 ; however, such an activity for the enzyme has yet to be demonstrated unequivocally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation